An Investigation into Teachers’ and Students’ Attitudes towards the Use of Visual Aids in Teaching and Learning Vocabulary at Le Quy Don Gifted High School, Dien Bien - Nguyễn, Hạnh Tuyết (ĐHNN, 2017)
This study aims at finding out the attitudes of the teachers and students at Le Quy Don gifted high school in Dien Dien towards the use of visual aids in teaching and leaning English vocabulary. In the study, the quantitative and qualitative methods are em (...)